Built environment and social well-being: How does urban form affect social life and personal relationships?. (April 2018) - Mouratidis, Kostas
Abstract: Personal relationships are among the most influential factors for achieving a happy life. Yet, there is insufficient empirical evidence on the role of the built environment in social life and personal relationships. This paper investigates how the urban form affects social life and personal relationships by applying structural equation models to survey data collected in Oslo metropolitan area. Results indicate that residents of compact neighborhoods are significantly more satisfied with their personal relationships compared with residents of low-density suburban neighborhoods. Shorter distances to the city center, higher densities, and mixed land uses are found to positively contribute to overall social well-being. Path analysis as well as qualitative analysis suggest that compact urban forms enable residents to maintain larger networks of close relationships, socialize more frequently with friends and family, receive stronger social support, and enjoy increased opportunities to make new acquaintances. Highlights: The built environment can influence social well-being. Compact urban forms may increase satisfaction with personal relationships. Shorter distances facilitate larger social networks and more frequent socializing. Higher densities and 'third places' increase opportunities to meet new people. Findings contribute to debates on quality of life and urban sustainability.